1982
DOI: 10.1111/j.1348-0421.1982.tb00169.x
|View full text |Cite
|
Sign up to set email alerts
|

Keratinolytic Fungi in Egyptian Soils

Abstract: The frequency of occurrence of keratinolytic fungi in seventy soil samples, collected from different sites in Upper Egypt and in the coastal area of the Mediterranean, was determined by baiting with human and animal hairs and pigeon feathers.Twenty-one species, in addition to an unidentified species, which belong to sixteen genera were collected. Chrysosporium indicum, C. tropicum, C. keratinophilum, and Microsporum gypseum were the most frequent fungal species recovered from the baited soils.The soil samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

1986
1986
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…The distribution and abundance of keratinophilic fungi in relation to the presence of organic materials in soil and different soil factors has been well studied [1–7]. It is also recognized that the distribution of keratinophilic fungi varies in the soil of different locations and the dominant species in any soil or dust may change with time [1–13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The distribution and abundance of keratinophilic fungi in relation to the presence of organic materials in soil and different soil factors has been well studied [1–7]. It is also recognized that the distribution of keratinophilic fungi varies in the soil of different locations and the dominant species in any soil or dust may change with time [1–13].…”
Section: Discussionmentioning
confidence: 99%
“…They found that elementary schools are more contaminated with keratinophilic fungi including dermatophytes than preparatory schools. Chrysosporium species are the most common keratinophilic fungi isolated from soils in many parts of the world including Egypt, Spain, Israel, Kuwait, India and New Guinea [8, 10–13, 23]. Filipello Marchisio reported the isolation of Chrysosporium spp., M. gypseum and T. ajelloi from children's sandpits in the city of Turin in Italy [24] and emphasized the potential risk of cutaneous mycoses for children playing in the sandpits or in public parks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In natural environments, the presence of keratin-associated fungi depends on the availability of keratinic substrata of animal or human origin [63]. The constant flow of such organic matter has been associated with the distribution of keratinolytic fungi in environments such as arable soils [64][65][66][67], sewage sludge and river bottom sediments [68,69], compost [70], bird feathers [71], the deposits of free-living rodents [72], the nests of water birds [73], and pellets of birds of prey [74].…”
Section: Discussionmentioning
confidence: 99%
“…Nuestras expectativas, estimaron un mayor número de aislamientos de Onygenales y taxa relacionados en todas los escalones altitudinales, sin embargo, nuestros resultados demuestran que las condiciones climáticas invernales y la altura pueden afectar su prevalencia en los meses fríos. El aislamiento de especies de Chrysosporium, Trichophyton, Malbranchea y Geomy-ces, son frecuentemente reportadas por diferentes autores en muchos países y climas, incluyendo las zonas antárticas (Alteras & Evolceanu, 1969;Abdel-Fattah et al,1982;Cano et al, 1985;Caretta et al,1992;Mercantini et al,1993) El clima antártico, considerado como un desierto frío, coincidentemente semeja en muchos aspectos al andino, que presenta bajas temperaturas, periodos cortos de crecimiento de los microorga-nismos, reducción de hábitat y escasa o nula pluviosidad en las latitudes estudiadas. Sin embargo, los integrantes del género Auxarthron, parecen tener una distribución más restringida, debido a que no son reportados con mucha frecuencia y aparentemente se han detectado mayoritariamente en el hemisferio norte, como en USA, Europa y Asia.…”
Section: B) Onygenales Queratinofílicas/liticas Y Anamorfos Asociadosunclassified